The Future Is Now—Prospective Study of Radiosurgery for More Than 4 Brain Metastases to Start in 2018! - Roberge, David; Brown, Paul D.; Whitton, Anthony; O'Callaghan, Chris; Leis, Anne; Greenspoon, Jeffrey; Smith, Grace Li; Hu, Jennifer J.; Nichol, Alan; Winch, Chad; Chan, Michael D. (Frontiers in Oncology, 2018)
Stereotactic radiosurgery (SRS) has replaced whole brain radiotherapy (WBRT) as standard therapy for most patients with four or fewer brain metastases due to improved cognitive outcomes and more favorable health related quality of life (QoL). Whether SRS or WBRT is the optimal radiation modality for patients with five to fifteen brain metastases remains an open question. Efforts are underway to develop prospective evidence to answer this question. One of the planned trials is a Canadian Cancer Trials Group (CCTG)-lead North American intergroup trial. In general cancer treatments must have two basic aims: prolonging and improving QoL. In this vein, the selection of overall survival and QoL metrics as outcomes appear obvious. Potential secondary outcomes are numerous: patient/disease related, treatment related, economic, translational, imaging and dosimetric. In designing a trial, one must also ponder what is standard WBRT — specifically should it be associated with memantine. With the rapid accrual of an intergroup trial of hippocampal-sparing WBRT, we may find that the standard WBRT regimen changes in the course of planned trials. As up-front radiosurgery is increasingly used for more than 4 brain metastases without high level evidence, we have a window of opportunity to develop high quality evidence which will help guide our future clinical and policy decisions.